Evaluating Wildlife as a Potential Source of Salmonella serotype Newport (JJPX01.0061) Contamination for Tomatoes on the Eastern Shore of Virginia. (17th June 2013) - Gruszynski, K.; Pao, S.; Kim, C.; Toney, D.; Wright, K.; Ross, P. G.; Colon, A.; Levine, S.
Summary Eastern Shore of Virginia red, round tomatoes contaminated with Salmonella serotype Newport pattern JJPX01.0061 have been a source of several multistate outbreaks within the last 10 years. No source of the contamination has yet been identified. The goal of this study was to evaluate wildlife as a potential source of contamination. Faecal samples from deer, turtles and birds were collected between November 2010 and July 2011 from seventeen locations on the Eastern Shore of Virginia. A total of 262 samples were tested for the presence of Salmonella using an enzyme‐linked immunosorbent assay (ELISA). A total of 23 (8.8%) samples tested positive for Salmonella spp. and were further characterized by serotyping and pulsed‐field gel electrophoresis (PFGE) subtyping. Overall, twelve serotypes were identified, including Salmonella serotype Javiana, another common serotype associated with tomato‐related outbreaks. Only one avian sample collected in July 2011 was determined to be positive for S. Newport pattern 61. This sample was collected from the ground at a site where birds, mostly gulls, were congregating. Although many of the avian samples from this site were dry, the site yielded eleven positive Salmonella samples. This suggests that certain Salmonella serotypes may persist in the environment despite extreme conditions. The recovery of one Newport pattern 61 isolate alone does not yield much information regarding the environmental reservoirs of this pathogen, but when combined with other data including the recovery of several isolates of Javiana from birds, it suggests that birds might be a potential source of Salmonella contamination for tomatoes on the Eastern Shore.